(untitled) (Baghdad Science Journal, 2006)
I have studied the relationship between blood groups in humans and disease Cutaneous injury for the first time in Iraq study showed the presence of a significant statistical relationship between them leather Bmsoy in hospitals in Baghdad and its suburbs